2018
DOI: 10.1016/j.epsl.2017.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Sound velocities and density measurements of solid hcp-Fe and hcp-Fe–Si (9 wt.%) alloy at high pressure: Constraints on the Si abundance in the Earth's inner core

Abstract: International audienceWe carried out sound velocity and density measurements on solid hcp-Fe and an hcp-Fe–Si alloy with 9 wt.% Si at 300 K up to ∼170 and ∼140 GPa, respectively. The results allow us to assess the density (ρ ) dependence of the compressional sound velocity (VPVP) and of the shear sound velocity (VSVS) for pure Fe and the Fe–Si alloy. The established VPVP–ρ and VSVS–ρ relations are used to address the effect of Si on the velocities in the Fe–FeSi system in the range of Si concentrations 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 45 publications
8
50
3
Order By: Relevance
“…Similar to the trends in v D , our reported v S for hcp-Fe agrees well with Mao et al (2001), Lin et al (2005), Mao et al (2008), Liu et al (2016), and it is only the 136 GPa data point of Gleason et al (2013) that appears to deviate significantly from these trends. The IXS studies by Antonangeli et al (2018) and Ohtani et al (2013) report v S curves based on their determined v P and existing equations of state (Dewaele et al, 2006;Sakai et al, 2014). The v S of Antonangeli et al (2018) and Ohtani et al (2013) trend respectively ∼5% and ∼11% above our reported v S for hcp-Fe, which is a significant deviation.…”
Section: Ironcontrasting
confidence: 47%
See 2 more Smart Citations
“…Similar to the trends in v D , our reported v S for hcp-Fe agrees well with Mao et al (2001), Lin et al (2005), Mao et al (2008), Liu et al (2016), and it is only the 136 GPa data point of Gleason et al (2013) that appears to deviate significantly from these trends. The IXS studies by Antonangeli et al (2018) and Ohtani et al (2013) report v S curves based on their determined v P and existing equations of state (Dewaele et al, 2006;Sakai et al, 2014). The v S of Antonangeli et al (2018) and Ohtani et al (2013) trend respectively ∼5% and ∼11% above our reported v S for hcp-Fe, which is a significant deviation.…”
Section: Ironcontrasting
confidence: 47%
“…A variety of studies have investigated the sound velocities of iron-silicon alloys at 300 K (Lin et al, 2003;Badro et al, 2007;Mao et al, 2012;Ono, 2013;Liu et al, 2014;Antonangeli et al, 2018;Sakairi et al, 2018). Silicon is found to increase the compressional velocity of hcp-Fe, but the effect of silicon on hcp-Fe's shear velocity is debated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we apply a linear mixing model. Badro et al (2007) propose linear mixing should hold for hcp-iron alloyed with low concentrations of light elements, and this approach has been applied to various solid iron alloys (e.g., Antonangeli et al, 2010Antonangeli et al, , 2018Badro et al, 2007;Fiquet et al, 2009;Ohtani, 2013). Linear mixing is therefore a reasonable approximation for a mixing of hcp-Fe, hcp-Fe 0.91 Ni 0.09 , and hcp-Fe 0.8 Ni 0.1 Si 0.1 .…”
Section: Seismic and Experimental Constraints On Core Composition 53mentioning
confidence: 99%
“…Consequently, the interpretations of the changes in the linear physicomechanical properties of the material due to deformation (pressure increase) are incorrect and unacceptable. Although in countless published articles including magazines of Category 1 (Antonangeli et al, 2018;Bin & Xiaojing, 2018;Channing et al, 2015;Chatterjee et al, 2017;Fischer et al, 2018;Guliyev, Akbarov, et al, 2018;Litasov & Shatskiy, 2016;Prescher et al, 2015) and in generalized monographs and textbooks (Anderson,…”
Section: The "Key" To Geomechanical Analysismentioning
confidence: 99%